Fazlur Rahman's Approach to the Major Themes of the Qur'an and Western Interpretation of the Qur'an - Muhammad Adip Fanani; Ach Fawaid; M Iqbal Abdurrohman (Penerbit Hellow Pustaka, 2024)
In the Islamic tradition, the development of Islamic studies is very interesting to continue to study, in the form of literature by western orientalists. This started after there was cultural contact between Islam and Christianity in the western world. Fazlur Rahman was a Muslim scholar who taught in the Western world (1332-1408 H/1919-1988 AD). He really knows the ins and outs of Orientalist studies by Western scholars, he studied at the University of Chicago, United States. One of Rahman's interesting studies discussed is, Major Themes of the Koran. He opposed the interpretation of the Qur'an carried out by orientalists such as Geiger, Theodor and Wansbrough, who considered that the Qur'an was only the work of the Prophet Muhammad and not from Allah SWT. In this article, we will discuss the main contents of the book Major Themes of the Qur'an, there are eight main points of Fazlur Rahman's thoughts and western orientalist interpretations of the Al-Qur'an.